Serological evidence of MERS-CoV and HKU8-related CoV co-infection in Kenyan camels - Wei Zhang; Xiao-Shuang Zheng; Bernard Agwanda; Sheila Ommeh; Kai Zhao; Jacqueline Lichoti; Ning Wang; Jing Chen; Bei Li; Xing-Lou Yang; Shailendra Mani; Kisa-Juma Ngeiywa; et al. (Emerging Microbes and Infections)
Dromedary camels are important reservoir hosts of various coronaviruses, including Middle East respiratory syndrome coronavirus (MERS-CoV) that cause human infections. CoV genomes regularly undergo recombination during infection as observed in bat SARS-related CoVs. Here we report for the first time that only a small proportion of MERS-CoV receptor-binding domain positive (RBD) of spike protein positive camel sera in Kenya were also seropositive to MERS-CoV nucleocapsid (NP). In contrast, many of them contain antibodies against bat HKU8-related (HKU8r)-CoVs. Among 584 camel samples that were positive against MERS-CoV RBD, we found only 0.48 (8.22%) samples were also positive for NP. Furthermore, we found bat HKU8r-CoV NP antibody in 73 (12.5%) of the MERS-CoV RBD positive and NP negative samples, yet found only 3 (0.43%) of the HKU8r-CoV S1 antibody in the same samples. These findings may indicate co-infection with MERS-CoV and a HKU8r-CoV in camels. It may also raise the possibility of the circulation of a recombinant coronavirus virus with the spike of MERS-CoV and the NP of a HKU8r-CoV in Kenya. We failed to find molecular evidence of an HKU8r-CoV or a putative recombinant virus. Our findings should alert other investigators to look for molecular evidence of HKU8r-CoV or recombinants.